Navigating Nepal’s Economic Landscape in the Context of South Asia: a Deep-Dive into GDP Growth, Inflation, Trade Balances, and Industrialization Challenges in the Region - Joshi, Binod; Adhikari, Gyan Mani (Journal of Business and Social Sciences, 2024)
South Asia, hosting over 1.9 billion people, represents one of the world’s most economically dynamic yet unevenly developed regions. While economies like India and Bangladesh exhibit robust growth, others, including Nepal, face significant challenges stemming from structural constraints. Nepal, a landlocked country with a population of approximately 32 million, is uniquely positioned within this regional economic landscape. It grapples with dependencies on agriculture, remittances, and imports, alongside limited industrialization and infrastructure deficits. This article analyzes Nepal’s economic performance through a comparative lens, evaluating key indicators such as GDP growth, inflation, trade balance, and foreign direct investment (FDI). Nepal’s moderate GDP growth of 4.5% in 2023 contrasts with higher regional averages, reflecting its challenges in economic diversification and reliance on low-value-added exports. Inflationary pressures, driven by import dependencies, and persistent trade deficits averaging USD 2 billion annually further constrain its growth potential. Meanwhile, FDI inflows remain modest due to regulatory and infrastructural bottlenecks, despite the country’s untapped potential in sectors like hydropower and tourism. The article highlights Nepal’s opportunities for sustainable growth, emphasizing the need for infrastructure investment, regional trade integration, and targeted economic reforms to attract FDI. By harnessing its natural resources, strategic location, and cultural assets, Nepal can strengthen its position within South Asia’s economic ecosystem, fostering resilience and long-term development.